The relevance of online dispute resolution in the Islamic finance industry in Malaysia - Olalekan, Omoola Sodiq (Ahmad Ibrahim Kuliyyah of Laws, International Islamic Universiry Malaysia, 2015)
This research aims to explore the relevance of Online Dispute Resolution (ODR) in the resolution of Islamic finance disputes in Malaysia. Stemming from the legal uncertainties in the resolution of Islamic finance disputes in the Malaysian civil courts and existing Alternative Dispute Resolution (ADR) institutions, access to justice for offline and online financial consumers in Malaysia has been in curtailed. This study examines the existing dispute resolution mechanisms available to Islamic finance consumers and the feasibility of adopting ODR mechanism for the industry. The research adopts doctrinal method to expound the convergence of key concepts such as ADR, internet and e-commerce in the 21st Century. In addition, relevant legislations and Islamic legal concepts in contemporary dispute resolution practices and theories are discussed in relation to ODR in the industry. Analysis of existing ODR best practices in other jurisdictions has been done to explore the economic and judicial benefits of ODR in the Industry. Court decongestion, resolution of small claims, fast and cheap mechanisms are few of the benefits of ODR which is capable of ensuring consumer confidence, trust and sustainable growth for the Islamic finance industry in Malaysia. This research finds that ODR is relevant to the Sharī'ah underpinnings and Islamic legal maxims which are the basis of Islamic finance transaction and dispute resolution. Therefore, borrowing a leaf from existing ODR best practices such as Equifax and Cybersettle, this will be a huge step in creating access to justice for online and offline financial consumers in the Islamic finance industry in Malaysia. This innovation however requires regulatory and institutional readjustment towards operationalizing ODR under the Financial Ombudsman Scheme (FOS) provided under Islamic Financial Services Act (IFSA2013) . This is in addition to efforts towards inter-disciplinary collaboration in creating a web-enabled portal for submission and resolution of finance disputes in Malaysia.